2015
DOI: 10.1007/s13196-015-0146-2
|View full text |Cite
|
Sign up to set email alerts
|

Feeding rate of termites in wood treated with borax, acetylation, polystyrene, and smoke

Abstract: Mindi (Melia azedarach) wood with density of 0.43 g/cm 3 from Indonesia and sugi (Cryptomeria japonica) wood with density of 0.34 g/cm 3 from Japan were treated with borax preservative, acetylation, polystyrene, and smoke. Treated and untreated wood samples were tested for resistance against subterranean termite (Coptotermes curvignathus) and dry wood termite (Cryptotermes cynocephalus) in the laboratory according to Indonesian standards. In addition to determining resistance of treated woods to termite attack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 6 publications
6
14
0
Order By: Relevance
“…The average weight loss of the three types of untreated wood was 46.7% and that of polystyrene-treated wood samples was 9.0%, indicating that polystyrene-treated wood had much better resistance than untreated wood to subterranean termite attack. This result was in line with Hadi et al [ 6 , 16 ]. Untreated mangium had the lowest weight loss compared with sengon and pine, and these results were in line with the rating of wood resistance against termite attack.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The average weight loss of the three types of untreated wood was 46.7% and that of polystyrene-treated wood samples was 9.0%, indicating that polystyrene-treated wood had much better resistance than untreated wood to subterranean termite attack. This result was in line with Hadi et al [ 6 , 16 ]. Untreated mangium had the lowest weight loss compared with sengon and pine, and these results were in line with the rating of wood resistance against termite attack.…”
Section: Discussionsupporting
confidence: 93%
“…The order of these values is related to the wood density, from lower to higher values. Lower-density wood was more easily penetrated by styrene monomer, borax, and acetic anhydride because more voids were present compared to higher-density wood [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the pine resin is responsible for the natural biological resistance of the tree due to recalcitrant chemical compounds like phenols and terpenes (Ljunggren et al, 2020), it was expected that the resin impregnated wood would show this effect. Previous studies on woods treated by in situ polymerization showed mass losses in the 6.7-9.6 % and 3-5 % range for hardwoods (Gascón-Garrido et al, 2013;Scholz et al, 2010) and softwoods, respectively (Scholz et al, 2010;Gascón-Garrido et al, 2013;Hadi et al, 2015;Acosta et al, 2020b). According to Venäläinen et al (2014) a mass loss above 10 % (as in the current study) indicates structural impairment in wood specimens exposed to accelerated decay tests with soil contact.…”
Section: Termite Resistancesupporting
confidence: 65%
“…Yatagai et al [9] reported that wood vinegars made from mixed chips of Cryptomeria japonica and Pseudotsuga menziesii (wood vinegar A), Quercus serrata (wood vinegar B), and Pinus densiflora (wood vinegar C) exhibited high termiticidal activities against Reticulitermes speratus. Some chemical modification methods on wood have also been developed, including acetylation [10], furfurylation [11], impregnation with polystyrene [12], impregnation with methyl methacrylate [13], as well as smoked wood [14].…”
Section: Introductionmentioning
confidence: 99%